Docências no Colégio de Aplicação da UFSCar: uma etnografia dos saberes e das identidades que inspiram uma outra educação dos 0 aos 10 anos. - Botega, Giovana Alonso (Universidade Federal de São Carlos, 2026)
The study entitled “Teaching Practices at the UFSCar Laboratory School: an ethnography of the knowledge and identities that inspire another form of education for children aged 0 to 10” aimed to “analyze how the training and professional development of teachers at the UFSCar Laboratory School, in their work with babies and young children, produce forms of knowledge and teaching identities that can inspire the education of older children.” Among the specific objectives of the investigation, the following stand out: (1) to map and analyze the training process (initial and continuing education) of teachers at the UFSCar Laboratory School; (2) to map and analyze teachers’ conceptions and pedagogical practices; (3) to analyze teachers’ identities and knowledge; and (4) to understand how early childhood education practices can inform pedagogical practices with older children. The study sought to answer the following question: “In what ways can the knowledge and identities constructed by teachers of babies and young children at the UFSCar Laboratory School contribute to rethinking the education of older children?” The hypothesis was that the knowledge and teaching identities developed by these teachers offer contributions to rethinking pedagogical practices aimed at older children within a broader perspective of childhood education. This is because such practices are grounded in democratic, dialogical, and respectful approaches built collaboratively in everyday interactions with different subjects. Considering factors such as years of experience, professional background, spaces, materials, and conceptions, these practices allow for a rethinking of education for older children. The research was characterized as qualitative in nature, based on ethnography (Geertz, 1989; 2004; André, 2008; Oliveira, 2013; Reis & Mendes, 2018; Silva & Silva, 2021), and employed various procedures for data production, collection, and analysis, including interviews, field journals, document review and analysis, as well as observations of daily life at the UFSCar Laboratory School. The data produced were analyzed and interpreted using Content Analysis (Bardin, 2011). The theoretical framework of the study is grounded in Childhood Studies and the Pedagogies of Childhood—referred to here as Pedagogies of Childhoods—drawing on the work of Rocha (1998, 1999), Kishimoto and Oliveira-Formosinho (2007), and Oliveira-Formosinho (2013). Among the main findings, the construction of a plural teaching identity stands out, shaped by diverse experiences, including working within a Laboratory School—a context that integrates teaching, research, and extension. The development of listening, dialogue, and respect for children emerges as a result of an identity built on exchange, collaboration, and commitment to early childhood education. Teaching knowledge in early childhood education is also highlighted, going beyond the ability to teach babies and young children to encompass understanding who these subjects are, how they develop, what they need, and what they desire. The study also indicates that teaching practices with babies and young children are constructed in practice, through interaction with these subjects and with other teachers, involving autonomy and flexibility in pedagogical work. Finally, another key finding is the identification of essential working conditions in early childhood education, including the availability of resources and materials, appropriate ratios of children to adults, and workload. These conditions can either support or limit planning, creativity, and teachers’ professional development. Thus, it is argued that the training and professional development of teachers at the UFSCar Laboratory School, in their work with babies and young children, produce knowledge and teaching identities that inspire the education of older children in ethical, political, and aesthetic terms. In doing so, they contribute to envisioning a different kind of school—one built collectively and respectful of all children, of all ages.
Teaching practices at UFSCar’s Laboratory School: An ethnography of the knowledge and identities that inspire an alternative education for children aged 0 to 10"
Keywords: Formação de Professores; Desenvolvimento profissional; Identidade docente; Infâncias; Educação Infantil; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade